PENENTUAN JUMLAH CAIRAN GLYCOL PADA PROSES DEHIDRASI GAS DI STASIUN PENGUMPUL GMB - Dwi Putri Lestari; Dian Dwi Lestari (CV. ADIBA AISHA AMIRA, 2025)
In the activities of the Station PT Pertamina Hulu Rokan Regional I Zone 4 Alpa Field uses a separation system to separate fluids and gas. One of them is by using a Dehydration Unit (DHU) in the form of scrubbers, contactors, glycol storage tanks, flash tanks, carbon filters, particular filters, heat exchangers, still columns, reboilers, and accumulators. The purpose of this study is to determine the factors that cause glycol losses. The method used in this study is to technically examine the condition of the dehydration device, control the circulation rate and calculate the circulation rate. The DHU system uses the chemical TEG (Triethylene Glycol) which will continue to be added during the dehydration process. The large number of chemical uses is due to the incompatibility of the wet gas inlet with the glycol flow rate in the contactor. In March 2023 the actual flow rate is 12 gallons per minute (GPM) during the regeneration process. Meanwhile, the flow rate obtained from the glycol circulation rate formula only reached 4.39 GPM. This causes frequent losses when contacting the contactor because the incoming circulation rate is not the same as that coming out. The use of glycol per day reaches 9.4 gallons, while the standard losses are only 0.3 gallons. From these results it is known that the difference in the glycol flow rate with the calculation results is that there is an error in the flow rate (pump rate) in the field which results in losses.